INTERVENSI ULTRASOUND DAN CLOSED KINEMATIC CHAIN EXERCISE LEBIH EFEKTIF DARIPADA INTERVENSI ULTRASOUND DAN OPEN KINEMATIC CHAIN EXERCISE DALAM MENURUNKAN NYERI PADA PASIEN OSTEOARTHRITIS LUTUT DENGAN SKOR NYERI 8-20 DI DAERAH BADUNG - Ni Made Deni Purnama; Nopi Andayani; Nila Wahyuni; I Wayan Sugiritama (Majalah Ilmiah Fisioterapi Indonesia, 2017)
ABSTRACT To reduce pain in patients with osteoarthritis of the knee can be given intervention ultrasound and closed kinematic chain exercises and ultrasound intervention and open kinematicchain exercise . This study is an experimental two group pre and post test design with the 20 samples were divided into 2 groups . Measurement decrease in knee pain was measured using a scale of Western Ontario McMaster Universities Osteoarthritis Index ( WOMAC). The result of paired t -test in group 1 test results obtained p = 0.000 , while in Group 2 showed p = 0.000 . In different test the difference between Group 1 with Group 2 using independent sample t -test was obtained p = 0.000 ( p < 0.05 ) , it can be concluded that the intervention ultrasound and closed kinematic chain exercise is more effective than intervention ultrasound and exercise in the open kinematic chain reducing pain in patients with osteoarthritis knee pain score 8-20 in the Badung area . Keywords : Ultra Sound , Closed Kinematic Chain Exercise , Open Kinematic Chain Exercise , pain